Valida????o do teste de atividade de vida di??ria-glittre em indiv??duos com a doen??a de Parkinson - Silva, Dayse Danielle de Oliveira (2018)
Objectives: Study I - To analyze the psychometric properties of the Unified Parkinson's Disease Rating Scale (UPDRS). Study II - Analyze the construct validity and the discriminatory power and verify if the Daily Life Activity-Glittre test (AVD-Glittre) is able to differentiate the stages of Parkinson's Disease (PD). Methods: Study I - systematic review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). The searches in PubMed, SciELO, PsycINFO, LILACS, PEDro and Cochrane Central Register of Controlled Trials databases occurred between March 1 and May 31, 2017, using the terms "Parkinson's Disease", "Unified Parkinson's Disease Rating Scale "" UPDRS "," outcome assessment "," psychometrics "," reliability "and" reproducibility ", including suggested synonyms, without language restrictions. Study II - cross-sectional, observational study performed at the Respiratory Exercise and Health Laboratory (LERES) at the University of Par??-UEPA from May 2016 to August 2016. Thirty individuals with PD (GP), and 19 healthy individuals in the control group (CG) were submitted to the study. Age from 50 to 80 years, without sex restrictions, hemodynamically stable (BP <140mmHg x 90mmHg), cognitively preserved. All participants had the following parameters before, during and after the tests: Blood Pressure (BP), Heart Rate (HR), Peripheral Oxygen Saturation (SpO2) and effort perception, as well as the perception of fatigue of lower members, by the Modified Borg Scale. Participants of the GP, after the application of the AVD-Glittre test, also underwent UPDRS, the 6-minute Walk Test (6MWT) and the 10-meter Walk Test (TC10m). Results: Study I - 19 studies were analyzed. The internal consistency for sections I to IV presented strong positive evidence. The reproducibility of section IV presented strong negative evidence. All sections presented strong negative evidence for content validity; in the hypothesis test of sections II and III, strong positive evidence was observed. The AVD-Glittre test presented a moderate positive correlation with section II (rho = 0.371, p = 0.043), a moderate to strong positive correlation with section III (rho = 0.658, p = 0.000) and a moderate correlation with the total UPDRS score (rho = 0.552; p = 0.002). There was a negative correlation between the AVD-Glittre test and the 6MWT (rho - 0.772, p <0.001), and a positive correlation, with a strong magnitude with the TC10m (rho = 0.854, p <0.001). The area under the ROC curve (AUC) obtained was 0.855 (confidence interval: 0.753 to 0.957, p = 0.000), characterizing the test as a good discriminatory instrument to differentiate individuals with PD from healthy subjects. Conclusions: Sections II and III presented reliability evidence to assess ADLs and motor performance of individuals with PD, respectively, however the correlation with the AVD-Glittre test was of moderate magnitude. The AVD-Glittre test proved to be valid to assess functional capacity, with discriminatory power to differentiate patients from healthy, but was not able to differentiate the various stages of PD.